Use and misuse of forest income by rural communities in Cameroon - Lescuyer, G.; Mbarga, H.N.; Logo, P.B. (2008)
Since 1996, Cameroon has been redistributing a share of Annual Forest Royalties (AFF) to villages/communities, with the aim of increasing rural people’s standards of living. However, its applicationhas been widely criticized. Our study is based on a sample of nine communities in the Cameroon forest belt. We found that:a significant part of AFF does not reach communities; 3 villages out of 9 add other incomes to AFF payments in order to carry out collective investments; and 3 other villages were able to justify the complete use of their AFF. This relative success in the establishment of a decentralized mechanism for forest incomemanagement indicates the need for strengthening the capabilities of communities in order to guarantee endogenous development.